Correlation Between Retinal Microvascular Abnormalities and Total Magnetic Resonance Imaging Burden of Cerebral Small Vessel Disease in Patients With Type 2 Diabetes - Zhang, Ying; Zhang, Zhixiang; Zhang, Min; Cao, Yin; Yun, Wenwei (Frontiers in Neuroscience, 2021)
Background and Purpose Diabetic retinopathy (DR) is one of the common microvascular complications in diabetes. The total MRI burden of cerebral small vessel disease (CSVD) has a high incidence in diabetics and is a marker of microvascular disease. The relationship between DR and CSVD is unclear. Therefore, this study aimed to explore the relationship between retinal microvascular abnormalities and the total MRI burden of CSVD in patients with type 2 diabetes. Methods The patients with type 2 diabetes who were hospitalized in Changzhou Second People′s Hospital affiliated to Nanjing Medical University from December 2019 to November 2020 were consecutively collected. All patients completed the retinal photography and cerebral MRI examination. The retinal vascular calibers were semi-automatically measured using Image J software and the total MRI burden score of CSVD was assessed. The relationship between retinal microvascular abnormalities and the total MRI burden of CSVD was analyzed. Results Of the 151 diabetic patients, 27 (17.9%) were mild DR and 40 (26.5%) were more than mild DR. In patients with the more than mild DR, the proportion of moderate to severe burden of CSVD was 75%, which was higher than that in patients with mild DR (48.1%) and NDR (26.2%). Patients with moderate to severe burden of CSVD were more likely to have narrowed retinal arterioles, widened retinal venules, and lower arteriole‑to‑venule ratio (105.24±8.42µm vs 109.45±7.93µm, 201.67±16.25µm vs 193.95±13.54µm and 0.52±0.05 vs 0.57±0.04 respectively, all P < 0.05) than patients with the mild burden of CSVD. The degree of DR (r=0.465, P<0.001) and CRVE (r=0.366, P<0.001) were positively correlated with the total MRI burden of CSVD. Further multivariate logistic regression analysis indicated that more than mild DR (OR, 4.383; P=0.028), CRAE (OR, 0.490; P=0.031), CRVE (OR, 1.475; P=0.041), after adjustment for age, smoking, alcohol consumption, hypertension, and other factors, were independent factors of patients with the moderate to severe burden of CSVD. Conclusion Retinal microvascular abnormalities in patients with type 2 diabetes are related factors for cerebral small vessel lesions. The degree of DR and the retinal vessel changes can be used as effective indicators to predict intracranial microcirculation lesions.